2018
DOI: 10.3389/fnagi.2018.00235
|View full text |Cite
|
Sign up to set email alerts
|

Gray Matter Volume and Cognitive Performance During Normal Aging. A Voxel-Based Morphometry Study

Abstract: Normal aging is characterized by decline in cognitive functioning in conjunction with extensive gray matter (GM) atrophy. A first aim of this study was to determine GM volume differences related to aging by comparing two groups of participants, middle-aged group (MAG, mean age 41 years, N = 16) and older adults (OG, mean age 71 years, N = 14) who underwent an magnetic resonance images (MRI) voxel-based morphometry (VBM) evaluation. The VBM analyses included two optimized pipelines, for the cortex and for the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 90 publications
8
63
0
Order By: Relevance
“…In normal aging, the posterior cerebellar lobes show accelerated volume reduction with respect to other structures [62], and this reduction may be more relevant to cognitive performance than typically shown by studies of diseased patients with cortical lesions. In line with our results, other recent studies including similarly aged and cognitively healthy cohorts [63][64][65] show involvement of the cerebellum in memory and executive function tests. Taken together, our findings showed structural correlates of cognitive performance in a well-characterized sample of subjects with normal cognition and normal AD CSF biomarker levels, providing evidence on the most vulnerable brain systems related to learning and memory in aging.…”
Section: Discussionsupporting
confidence: 93%
“…In normal aging, the posterior cerebellar lobes show accelerated volume reduction with respect to other structures [62], and this reduction may be more relevant to cognitive performance than typically shown by studies of diseased patients with cortical lesions. In line with our results, other recent studies including similarly aged and cognitively healthy cohorts [63][64][65] show involvement of the cerebellum in memory and executive function tests. Taken together, our findings showed structural correlates of cognitive performance in a well-characterized sample of subjects with normal cognition and normal AD CSF biomarker levels, providing evidence on the most vulnerable brain systems related to learning and memory in aging.…”
Section: Discussionsupporting
confidence: 93%
“…This may be explained by the fact that multiple factors can affect grey matter volume such as age, levels of education and brain reserve. It has been previously shown that smaller grey matter volumes in the frontal lobes associated with ageing are associated with worse performance on frontal lobe cognitive tests [54]. The neuropsychological assessment performed in this study mainly focused on temporal lobe cognitive functioning and not frontal lobe function.…”
Section: Discussionmentioning
confidence: 99%
“…Normal aging is also characterized by gray matter volume (GMv) loss (Ramanoël et al, ) with the frontal and temporal lobes being the regions with the highest degree of GM loss (Driscoll et al, ), which is also considered to be marker of neurodegeneration (Dong et al, ). Cross‐sectional studies have also revealed a regional relationship between GMv and cognition in cognitively unimpaired individuals (Duarte et al, ; Tuladhar et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Normal aging is also characterized by gray matter volume (GMv) loss (Ramanoël et al, 2018) with the frontal and temporal lobes being the regions with the highest degree of GM loss (Driscoll et al, 2009), which is also considered to be marker of neurodegeneration (Dong et al, 2015).…”
mentioning
confidence: 99%